Manajemen Konflik dalam Pendidikan: Pendekatan Kolaboratif di Sekolah - Zainal Arifin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study examines the implementation of a collaborative approach to conflict management in educational settings, particularly in schools. Conflicts in schools can stem from substantive factors, such as differing perspectives and policies, or emotional factors, including personality clashes. This research aims to explore collaborative strategies that emphasize open communication, active participation, and shared solutions. The method used is a qualitative literature review, where data is sourced from relevant journals, articles, and previous studies. The findings reveal that the collaborative approach effectively fosters a conducive and harmonious school environment. By involving key stakeholders—teachers, students, parents, and school management—this approach enables constructive conflict resolution and strengthens relationships among the parties involved. The study underscores the importance of improving communication skills, providing conflict management training, and ensuring sufficient resources to support this approach in schools.